The synergistic antitumor activity of 3-(2-nitrophenyl) propionic acid-paclitaxel nanoparticles (NPPA-PTX NPs) and anti-PD-L1 antibody inducing immunogenic cell death - Xiao-Chuan Duan; Li-Yuan Peng; Xin Yao; Mei-Qi Xu; Hui Li; Shuai-Qiang Zhang; Zhuo-Yue Li; Jing-Ru Wang; Zhen-Han Feng; Guang-Xue Wang; Ai Liao; Ying Chen; et al. (Taylor & Francis Group, 2021)
Cancer immunotherapy is a strategy that is moving to the frontier of cancer treatment in the current decade. In this study, we show evidence that 3-(2-nitrophenyl) propionic acid-paclitaxel nanoparticles (NPPA-PTX NPs), act as immunogenic cell death (ICD) inducers, stimulating an antitumor response which results in synergistic antitumor activity by combining anti-PD-L1 antibody (aPD-L1) in vivo. To investigate the antitumor immunity induced by NPPA-PTX NPs, the expression of both ICD marker calreticulin (CRT) and high mobility group box 1 (HMGB1) were analyzed. In addition, the antitumor activity of NPPA-PTX NPs combined with aPD-L1 in vivo was also investigated. The immune response was also measured through quantitation of the infiltration of T cells and the secretion of pro-inflammatory cytokines. The results demonstrate that NPPA-PTX NPs induce ICD of MDA-MB-231 and 4T1 cells through upregulation of CRT and HMGB1, reactivating the antitumor immunity via recruitment of infiltrating CD3+, CD4+, CD8+ T cells, secreting IFN-γ, TNF-α, and the enhanced antitumor activity by combining with aPD-L1. These data suggest that the combined therapy has a synergistic antitumor activity and has the potential to be developed into a novel therapeutic regimen for cancer patients.